2013
DOI: 10.1111/neup.12042
|View full text |Cite
|
Sign up to set email alerts
|

Novel neuronal cytoplasmic inclusions in a patient carrying SCA8 expansion mutation

Abstract: It has been reported that abnormal processing of pre-mRNA is caused by abnormal triplet expansion. Non-coding triplet expansions produce toxic RNA to alter RNA splicing activities. However, there has been no report on the globular RNA aggregation in neuronal cytoplasmic inclusions (NCIs) up to now. We herein report on an autopsy case (genetically determined as spinocerebellar atrophy 8 (SCA8)) with hitherto undescribed NCIs throughout the brain. NCIs were chiefly composed of small granular particles, virtually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
(24 reference statements)
1
11
1
Order By: Relevance
“…Similar changes were found in human autopsy tissue, with evidence for demyelination and axonal degeneration in deep cerebellar white matter (Fig B). These sites of white matter pathology are positive for RAN polySer, but not for polyGln (Fig B) and are consistent with white matter abnormalities previously found by imaging and neuropathology in SCA8 patients (Kumar & Miller, ; Kim et al , ; Yokoyama et al , ). In contrast, brain regions that did not show polySer aggregates in SCA8 BAC mouse cerebellum (Fig EV3A) and human cortical white matter (Fig EV3B) did not show evidence of demyelination.…”
Section: Resultssupporting
confidence: 89%
“…Similar changes were found in human autopsy tissue, with evidence for demyelination and axonal degeneration in deep cerebellar white matter (Fig B). These sites of white matter pathology are positive for RAN polySer, but not for polyGln (Fig B) and are consistent with white matter abnormalities previously found by imaging and neuropathology in SCA8 patients (Kumar & Miller, ; Kim et al , ; Yokoyama et al , ). In contrast, brain regions that did not show polySer aggregates in SCA8 BAC mouse cerebellum (Fig EV3A) and human cortical white matter (Fig EV3B) did not show evidence of demyelination.…”
Section: Resultssupporting
confidence: 89%
“…Neuronal loss and gliosis were found in the cranial motor nucleus with basophilic inclusions immunoreactive for TDP43, a protein causative of familial ALS. 10 These findings suggest that SCA8 occasionally affects upper and lower motor neurons, a prerequisite for a diagnosis of ALS.…”
Section: Discussionmentioning
confidence: 93%
“… 5 , 6 , 8 Several studies have suggested the involvement of upper and lower motor neurons in SCA8, but a positive association between SCA8 and ALS remains unestablished. 9 , 10 …”
mentioning
confidence: 99%
“…The pathogenic SCA8(CUG112) transcripts formed nuclear as well as perinuclear and cytoplasmic RNA foci in the larval eye-antennal discs (Fig. 3 A), which was similar to the RNA foci formed in SCA8 diseased human brain samples(38). The toxic RNA foci were predominantly localized in the nucleus along with a few cytoplasmic RNA foci.…”
mentioning
confidence: 89%